In vitro culture of Stryphnodendron adstringens Mart. Coville - Nogueira, Gabriela Ferreira; Paiva, Renato; Vargas, Daiane Peixoto; Herrera, Raírys Cravo; Rocha, Tainá Teixeira; Silva, Diogo Pedrosa Corrêa da (Plant Cell Culture & Micropropagation - ISSN 1808-9909, 2023)
Stryphnodendron adstringens (Mart.) Coville is a species native to Cerrado with high medicinal potential. It is an important tannin source, is used mainly due to its healing, anti-inflammatory, and anti-septic activities. Due to the difficulties in sexual propagation, the objective of this work was to study some aspects of its the in vitro culture. The concentration of salts influenced the establishment of the initial explant in vitro, with a higher percentage of germination in the culture medium without salts. The combination of concentrations of 1.0 mg L-1 BAP and 0.1 mg L-1 NAA promoted greater shoot formation, and the concentration of 2.0 mg L -1 IBA promoted greater histogenesis. The composition of the culture medium influenced the establishment and development of S. adstringens. Index terms: Native Brazilian tree; tissue culture; micropropagation; growth regulator